Analysis Of Youth Characteristics Not in Education, Employment, Or Training (NEET) - Ninik Srijani; Ramadhan Prasetya Wibawa; Intan Rafika Dewi; Ervi Aulia Rahma; Aning Prasetyo Sari (Economic Education Analysis Journal, 2023)
This study aims to determine the characteristics of NEET and the macro conditions in which the individual lives against the probability of an individual entering the NEET group (NEET status) in Madiun. This research uses a qualitative approach, with a purposive sample with certain considerations with informants a few 20 alumni of economics education in 2020-2022 who are not yet working. The results show factors that influence a person to become a NEET such as age, education and job qualifications needed in the field, and not having a link to work. Some informants are still choosing and sorting out the jobs to apply for, want to enjoy the process of consulting someone in the neighborhood, have fun instead of working and come from rich families. Informants have all the characteristics of NEET, namely not wanting to work and looking for work, anti-social, depending on other people to fill their days with less useful activities. The visible characteristics of NEETs are that they must fulfill their own needs, in order to actualize themselves. Starting from meeting physical needs, the need for security, being recognized by society, feeling affection, and being valued so that they are able to achieve the best version of themselves. Starting from improving relations with family, then trying to get out and socialize with society.